2022
DOI: 10.1111/cns.14052
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ADAMTS3 Suppresses Stemness and Tumorigenicity in Glioma Stem Cell

Abstract: Aims Glioblastoma multiforme (GBM) is the most aggressive type of human brain tumor, with a poor prognosis and a median overall survival of fewer than 15 months. Glioma stem cells (GSCs) have recently been identified as a key player in tumor initiation and therapeutic resistance in GBM. ADAMTS family of metalloproteinases is known to cleave a wide range of extracellular matrix substrates and has been linked to tissue remodeling events in tumor development. Here, we investigate that ADAMTS3 regulates GSC prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…ADAMTS3 participates in normal physiological processes, like the embryonic development, tissue remodeling and wound healing [ 48 ]. A study by Kim et al reported that ADAMTS3 was highly expressed in glioma stem cells and significantly correlated with its tumorigenic and proliferative activities [ 49 ]. However, at present, no study has reported the correlation between ADAMTS3 and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS3 participates in normal physiological processes, like the embryonic development, tissue remodeling and wound healing [ 48 ]. A study by Kim et al reported that ADAMTS3 was highly expressed in glioma stem cells and significantly correlated with its tumorigenic and proliferative activities [ 49 ]. However, at present, no study has reported the correlation between ADAMTS3 and HCC.…”
Section: Discussionmentioning
confidence: 99%